Education Nonviolence Through Child Friendly School - Zaenul Slam (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract This research described the education nonviolence through implementation of child friendly school in Junior High School 3 Majalengka, West Java Province. The research was qualitative. The data were collected through observation, interviews, and documentation. The subjects of the research were the principal, teachers, and students. Analysis of the data were through the three stages: data reduction, data presentation, and conclusion. Validity test of  the data used triangulation sources. The results show that education nonviolence had established the education to a peace culture, to create and encourage the peace in the minds of the students based on the  universal values of respect for life, liberty, justice, solidarity, tolerance, human rights and equality between them. Education  nonviolence  through  implementation of child friendly school in Junior High School 3 Majalengka was seen from the success of school management. Abstrak Penelitian ini memeberikan gambaran tentang pendidikan tanpa kekerasan melalui penerapan sekolah ramah anak di Sekolah Menengah Pertama (SMP) 3 Majalengka, Provinsi Jawa Barat. Penelitian ini adalah kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Subjek penelitian ini adalah kepala sekolah, guru, dan siswa. Analisis data dilakukan melalui tiga tahapan: reduksi data, penyajian data, dan kesimpulan. Uji validitas data menggunakan sumber triangulasi. Hasil menunjukkan bahwa pendidikan tanpa kekerasan telah membentuk pendidikan ke budaya perdamaian, untuk menciptakan dan mendorong kedamaian di dalam pikiran siswa berdasarkan nilai-nilai universal penghormatan terhadap kehidupan, kemerdekaan, keadilan, keakraban, toleransi, hak asasi manusia dan kesetaraan di antara mereka. Pendidikan tanpa kekerasan  melalui penerapan sekolah ramah anak di SMP 3 Majalengka dilihat dari kesuksesan manajemen sekolah. How to Cite : Slam, Z. (2016).  Education  Nonviolence Through   Child Friendly School. TARBIYA: Journal of Education in Muslim Society, 3(2), 186-204. doi:10.15408/tjems.v3i2.4983. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4983